Implementation of the Hard-Decision Low Density Parity Check Codes in A 0.13Âµm CMOS Process - P. Pongcol, Daryl; B. Madronial Jr., Roberto; Joy L. Gerasta, Olga; A. Hora, Jefferson; Banuchandar, J. (International Journal of Engineering and Technology, 2018)
This paper presents a simple and efficient implementation of a Low Density Parity Check (LDPC) error-correcting code, using the hard-decision decoding algorithm in a 0.13 Âµm TSMC CMOS process. The encoder and decoder modules were simulated by transmitting the correct 8bit code words, and letting it pass through a test bench module that corrupts one or more bits of the channel data, then allowing the decoder to correct the corrupted channel data. The system is able to correct a single bit error with 1 or 2 iterations only. Hence for a clock of 50MHz, the system can detect and correct more than 42 bit errors per 1 KB of data, which is just the goal of this research. Implemented through Verilog HDL using Synopsys Design, the design is simple in a sense that it does not use sophisticated encoding and decoding algorithms and the H- matrix used is a simple Â½ code rate (4,8)- regular matrix and thus will result to a small scale and non-congested full-parallel architecture. It only measured 6.29 mm2 chip area. For a supply voltage of 1.32 V, the total power of only 138.64 ÂµW implied very low power consumption.Â Â